Dupilumab and Alopecia Areata: A Possible Combined or Disturbance Therapy? A Review of the Literature - Michela Starace; Stephano Cedirian; Federico Quadrelli; Francesca Pampaloni; Tullio Brunetti; Marco Adriano Chessa; Carlotta Gurioli; Bianca Maria Piraccini; Iria Neri (Mattioli1885, 2024)
Dupilumab, a monoclonal antibody targeting the IL-4 receptor subunit alpha, has revolutionized the treatment landscape for atopic dermatitis. This literature review delves into the intriguing relationship between atopic dermatitis and alopecia areata, exploring the dual impact of dupilumab on patients with these coexisting dermatological conditions. Our analysis of 25 relevant articles reveals a complex interplay where dupilumab can either exacerbate or ameliorate alopecia areata, depending on individual patient characteristics and pathogenic pathways. In our findings, while some patients experienced worsening of AA with dupilumab, others achieved remarkable hair regrowth, highlighting the double nature of its effects.